The Road to Iraq : the Making of a Neoconservative War. - Ahmad, Muhammad Idrees (Edinburgh scholarship online., 2014)
A rigorous investigation into the socio-political milieu that produced the Iraq war. Despite all that has been written on it, the Iraq war - its causes, agency and execution - has been shrouded in an ideological mist. Now, Muhammad Idrees Ahmad dispels the myths surrounding the war, taking a sociological approach to establish the war's causes, identify its agents and describe how it was sold. Ahmad presents a social history of the war's leading agents - the neoconservatives - and shows how this ideologically coherent group of determined political agents used the contingency of 9/11 to overwhelm a sceptical foreign policy establishment, military brass and intelligence apparatus, propelling the US into a war that a significant portion of the public opposed. The book includes an historical exploration of American militarism and of the increased post-WWII US role in the Middle East, as well as a reconsideration of the debates that John Mearsheimer and Stephen Walt sparked after the publication of The Israel lobby and US Foreign Policy.